Perancangan Sistem Pengendalian Kualitas di PT Bondi Syad Mulia - Try Fenni Wijayani; Jani Rahardjo (Jurnal Titra, 2013)
PT Bondi Syad Mulia is a company that engages in Hot Dip Galvanizing services using zinc liquid. The problem occurred in PT Bondi Syad Mulia was the current quality control system not yet well manage. Therefore, they had many customers’ complain and the management required the Quality Control Department to be an independent department.The purpose of this thesis is to plan a new quality control system. This control system is aimed for controlling product quality from the incoming materials (iron and steel), the production process and finish product outcome. Additionally, that system is divided into four main factors: new inspection planning system, managing and changing quality control division task, revision on company’s Standard Operational Procedure (SOP), and creating quality control plan. The revised SOP were prepared for galvanizing control, defect product control, incoming goods accepting and handling, galvanizing preparation and customer complain handling.